Whole genome sequence and annotation dataset of rare actinobacteria, Barrientosiimonas humi gen. nov., sp. nov. 39 T from Antarctica - Chong, Sin Yee; Azmi, Aida Azrina; Cheah, Yoke Kqueen (Elsevier, 2023)
Barrientosiimonas humi gen. nov., sp. nov. 39T is a rare actinobacteria strain isolated from the less explored extreme environment of the Antarctic soil. Here, we present the whole genome sequencing and annotation data from the high-quality draft genome of B. humi from Antarctica. The extracted genomic deoxyribonucleic acid (DNA) was sequenced using the PacBio Sequel sequencing platform, followed by the Illumina HiSeq sequencing system. Subsequently, the assembly data from Canu 1.7 and Pilon were subjected to bioinformatics analysis for genome annotation to analyze the entire genomic information of the sequences. Different bioinformatics analysis approaches were used to disclose a high-quality draft genome basis for B. humi and provided a better understanding of its biological and molecular functions. Note that 83,639 reads were predicted from its 3.6Mb genome size, with a guanine-cytosine content (GC) content of 72.39. The genome was assembled into two contigs, where the larger contig represents the chromosome and the smaller contig represents the plasmid. It is composed of 3,381 coding genes, with about 95 of them being functionally annotated. It consists of 3,318 coding sequences, one tmRNA gene, 57 tRNA genes, and five repeated regions. B. humi was evident, sharing a close sequence similarity with the species Demetria terragena and the family Dermacoccaceae. Gene Ontology (GO) functional classification indicated cell and cell parts were highly represented among the cellular component category; catalytic activity and binding were the most enriched processes within the molecular function category; metabolic and cellular processes were the most represented in the biological process category. Clusters of Orthologous Group (COG) functional classification revealed metabolism-related genes were highly enriched and mostly mapped to amino acid transport metabolism, transcription, energy production, and conversion. Moreover, the Kyoto Encyclopedia of Genes and Genomes (KEGG) functional classification reported that the metabolism process was the most represented KEGG pathway. There were 52 biosynthetic gene clusters involved in secondary metabolites biosynthesis, indicating B. humi has antibacterial, antifungal, cytotoxic, and inhibitor bioactivities. The dataset of the whole-genome sequence of B. humi has been deposited in the European Nucleotide Archive (ENA) repository under the accession number PRJEB44986 / ERP129097. The dataset of the genome annotation of B. humi had been deposited in Zenodo. The reported genomic sequence data for B. humi contributes comprehensive data to the current molecular information of the species, serving as a significant approach that facilitates the advancement of medicine.